Estudo clínico simples cego da ação cicatrizante da aloe vera como cobertura em lesões por pressão - Pinheiro, Julliana Dias (Universidade Federal do Tocantins, 2020)
The high prevalence of pressure injuries (LPP) in the hospital environment highlights the importance of new and effective intervention programs in the prevention and treatment of this injury. The use of herbal remedies has grown over the years in the health context, possibly coupled with the perception that the consumption of natural items is synonymous with wellbeing, quality of life and longevity; In this context, medicinal plants have shown to be a promising resource in the identification of new bioactive compounds. The objective was to analyze the use of Aloe vera-based coverage for the healing of LPP in hospitalized patients. A data survey was also performed through articles that show the efficacy of Aloe vera-based herbal medicine in the healing of tissue injuries, through systematic literature review in the electronic databases, LILACS, Medline, Web of Science. The results show the efficiency of Aloe vera in the cooperation of the process of repair and healing of tissue injuries, due to the presence of substances in the parenchyma of the leaves that stimulate tissue growth and cell regeneration. Thus, it is emphasized that the Aloe vera gel has anti-inflammatory properties promoting faster healing. We also found advantages in relation to the cost benefit, since the Aloe vera gel has low economic cost and easy access.